Penerapan Bimbingan Kelompok dengan Motode Permainan Kerjasama untuk Meningkatkan Penyesuaian Peserta Didik Kelas XI TP 1 di SMK Negeri 1 Adiwerna - Kaslani (JCOSE Jurnal Bimbingan dan Konseling, 2021)
The background of this research problem is the inability of students to make adjustments, resulting in self-adjustment in the low category. The purpose of this study was to determine the application of group guidance with cooperative game media to improve student adaptation. This type of research is a two-cycle action research. The sampling technique used was purposive sampling with students who had a low level of self-adjustment, namely 10 students in class XI TP 1. The results obtained regarding the adjustment of group members in the initial conditions were 38% or in the low conditions with a total of 10 students. The percentage of the level of self-adjustment given through group guidance with cooperative game media in the first cycle obtained a percentage of 76% in moderate conditions. Improvements from cycle I then given action in cycle II with the result of a percentage of 95% at a high level of self-adjustment of group members. The conclusion from this research is that the adjustment of group members can be improved through group guidance with the cooperative game method. The advice given to the principal is expected to facilitate counseling guidance teachers in developing media to provide services to students, and guidance and counseling teachers are expected to provide treatment (treatment) to students who have the ability to improve self-adjustment.